Pengaruh Campuran Etanol dan Xilena dengan Pertamax terhadap Durasi dan Ukuran Nyala Api Pembakaran Droplet - Aditiya Bambang Bagaskoro; Purwoko Purwoko (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The global demand for energy, particularly fuel oil, continues to increase along with the growth in the number of vehicles and industrial activity. However, limited fossil fuel reserves and the environmental impacts of their use have prompted various studies to find alternative fuels that are more environmentally friendly, efficient, and sustainable. In this context, ethanol and xylene have emerged as two potential fuel additive candidates. Ethanol is known as a biofuel derived from renewable sources and has a high octane rating and oxygen content that can support a more complete combustion process. On the other hand, xylene is an aromatic compound with a high octane rating that can improve combustion stability and reduce the risk of knocking or detonation in engines. This study aims to evaluate the effect of ethanol and xylene additions on the flame characteristics of Pertamax fuel, particularly in terms of flame duration and height. Through a laboratory experimental approach, observations were made on the combustion process of pure Pertamax and several fuel blends with varying ethanol and xylene contents. The results showed that pure Pertamax produced a flame with an average duration of 0.734 seconds and a flame height of 4.5 cm, while one of the best blends, namely the fourth blend containing ethanol and xylene, produced a flame duration of 1.084 seconds and a flame height of 5.7 cm. These findings indicate that the addition of ethanol and xylene can significantly improve combustion performance. These results not only enrich knowledge regarding the combustion characteristics of blended fuels, but also open up opportunities for the development of alternative fuel formulations that are more environmentally friendly, energy efficient, and support reducing dependence on fossil fuels in the future.